Evaluación e impacto socioeconómico del microcrédito otorgado a socios de la cooperativa de transportes camionetas “tres de marzo”, cantón Chimbo por la cooperativa de ahorro y crédito San José Ltda. periodo 2010 -2011 - Cruz Angamarca, Alexandra Jaqueline (2011)
The present investigation pursues to give to know the most outstanding aspects in the evaluation of the socioeconomic Impact from the negotiated microcredit’s to the partners of the cooperative of transports vans “March Three”, The microcredit has become one of the most important tools for these transport companies to foment its established business. By means of the analysis and study of this supposition is looked for to insert in the process of development of the credit, through the generation of information and studies on the impact, evolution and contribution of this product to the socio-economic development of the Canton Chimbo. In the realization of this work, a type of documental investigation was used (you interview) with the necessary procedures that it has happened (before-later) of the obtaining of the microcredit, where its specific objectives are; to diagnose, to analyze, to propose and to indicate the advantages and disadvantages of the evaluation of the impact economic partner, basing its justification the human factor and socioeconomic since it is the most important asset inside any organization and that of him it depends its existence and permanency in the labor market. They took into account some records that you/they served as pillar for the beginning from the concentrated study to the theoretical bases been founded in diverse approaches of several authors related with the topic in question processing and analyzing each one of the different focuses to try to give answer to the generated objectives of the position of the problem. Associated to the before exposed it is given a conclusion and a series of recommendations that pudieren to be the most profitable for the successful handling of the microcredit’s through the evaluation of the impact economic partner, trying to leave very defined that each cooperative should adapt the exposed recommendations if they felt pertinent in function to its interests or purpose of the same ones, chord to the activity and the objectives that it pursues each one without stopping to take into account the human factor and economic as main and vital resource for its subsistence and the training of its partners so that they improve its economic stability.